2014
DOI: 10.1093/nar/gku939
|View full text |Cite
|
Sign up to set email alerts
|

Survey of chimeric IStron elements in bacterial genomes: multiple molecular symbioses between group I intron ribozymes and DNA transposons

Abstract: IStrons are chimeric genetic elements composed of a group I intron associated with an insertion sequence (IS). The group I intron is a catalytic RNA providing the IStron with self-splicing ability, which renders IStron insertions harmless to the host genome. The IS element is a DNA transposon conferring mobility, and thus allowing the IStron to spread in genomes. IStrons are therefore a striking example of a molecular symbiosis between unrelated genetic elements endowed with different functions. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 81 publications
(139 reference statements)
1
13
0
Order By: Relevance
“…However, in these mobile elements, a transposase is located within the loop of the large hairpin. A recent genome survey found that IStrons were restricted to a few members of the Firmicutes and Fusobacteria (Tourasse et al, 2014 ). Unlike group I introns, IStrons invade many types of protein-coding genes and are often found without some, or all, of the IS components, making them appear more like a MITE.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, in these mobile elements, a transposase is located within the loop of the large hairpin. A recent genome survey found that IStrons were restricted to a few members of the Firmicutes and Fusobacteria (Tourasse et al, 2014 ). Unlike group I introns, IStrons invade many types of protein-coding genes and are often found without some, or all, of the IS components, making them appear more like a MITE.…”
Section: Resultsmentioning
confidence: 99%
“…The IS200/IS605 family of IS elements are unique among known IS elements in that they encode a HUH endonuclease that recognizes a terminal imperfect palindrome and then transposes it into a single strand of genomic DNA (He et al, 2013 ). They are also unique in that they have been found in IStrons (see Tourasse et al, 2014 , and references therein). This IS family also has the potential to transform or decay into a unique MITE-like structures called palindrome-associated transition elements (PATEs) (Dyall-Smith et al, 2011 ; Siguier et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Even for lytic viruses, data are accumulating on frequent integration into the host genomes, even if this process is spurious with respect to virus reproduction (Chiba et al 2011; Koonin 2010; Liu et al 2010). A striking example of fusion between distinct parasitic replicators are the IStrons which are hybrids between Group I self-splicing introns and insertion sequences, and combine properties of introns and DNA transposons (Tourasse et al 2014). Similarly, large DNA viruses often harbor self-splicing introns and serve as vehicles for their dissemination (Edgell et al 2011; Yoosuf et al 2012).…”
Section: The Replicator Paradigmmentioning
confidence: 99%